Engagement of portfolio manager in assessing relative priority of project activities: Authority or perspective matter?*. (September 2018) - Laslo-Roth, Roni; Hadad, Yossi; Keren, Baruch; Laslo, Zohar
Authority struggles are mostly coincident with relational conflicts that impede rational solutions and have destructive impacts on performance. This study revealed that disagreements with the portfolio manager about relative priority of project activities seem, to the project managers, to be groundless and are therefore suspected as authority matters. The results from implementation of a developed multiple-criteria decision-making simulation on a realistic field scenario showed that such conflicts may result from the wider perspective of the portfolio manager. Project managers' awareness of this insight may reduce the intensity of such conflicts and by that, decrease their negative effect on the performance.